PENGARUH MANAJEMEN KARIR TERHADAP KEPUASAN KARIS MELALUI KOMPETENSI PEGAWAI - Hengky Pangestu (Jurnal Manajemen dan Pemasaran Jasa, 2013)
The purpose of this research is to acknowledge the effect of a career management toward the career satisfaction through the career competency of the staff at Park Lane Hotel, Jakarta. The data samples of this research are random spread to the hotel staffs. Out of 125 respondents from all levels of staff positions in Park Lane Hotel, only 120 data are performed. The dataanalysis in this research is measured by Structural Equation Modelling with Amos 6.0. Due to data analysis, it is discovered that career management has a positive and significant effects toward the career satisfaction of the hotel staafs, as to the career management has no effect to the career competency of the hotel staffs. The career competency has positive and significant effect to the career satisfaction, and the career competency cannot mediated the relation between career management to the career satisfaction of the hotel staffs.The implication for the manager of the Park Lane Hotel, Jakarta is to give serious activities concerning the career management to the staff that will assist them to gain more knowledge of the update industry development to gain higher in the career satisfaction of the staffs. In the future research, it needs more details concerning the organization effect and individual and culture factors of the staffs.Keywords : career management, career satisfaction and career competency.